2012
DOI: 10.1074/jbc.m112.372789
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5-Bisphosphate (PtdIns(4,5)P2) Specifically Induces Membrane Penetration and Deformation by Bin/Amphiphysin/Rvs (BAR) Domains

Abstract: Background:The roles of anionic lipids in the actions of N-BAR domains are not fully understood. Results: PtdIns(4,5)P 2 specifically induces membrane penetration and self-association of N-BAR domains. Conclusion: PtdIns(4,5)P 2 is an important regulator of the membrane deforming activity of N-BAR domains. Significance: This study provides new insight into how PtdIns(4,5)P 2 in the plasma membrane regulates the endocytic function of N-BAR domain proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 71 publications
(92 reference statements)
2
49
0
Order By: Relevance
“…In particular, this model attributes a role in vesicle fission to a preference of BAR domain proteins for PI(4,5)P 2 over PI(4)P. This affinity difference has been supported by equilibrium lipid binding studies for endophilin (13,28). We found a marked influence of phosphoinositides on kinetics, although revealing no significant difference comparing PI(4,5)P 2 and PI(4)P in association or dissociation (Fig.…”
Section: Role Of Electrostatics In the Association Phase Of The Mechamentioning
confidence: 47%
See 1 more Smart Citation
“…In particular, this model attributes a role in vesicle fission to a preference of BAR domain proteins for PI(4,5)P 2 over PI(4)P. This affinity difference has been supported by equilibrium lipid binding studies for endophilin (13,28). We found a marked influence of phosphoinositides on kinetics, although revealing no significant difference comparing PI(4,5)P 2 and PI(4)P in association or dissociation (Fig.…”
Section: Role Of Electrostatics In the Association Phase Of The Mechamentioning
confidence: 47%
“…However, beyond qualitative kinetic characterization by surface plasmon resonance (SPR) (28), little is known about the timescales and mechanisms determining the kinetics of endophilin-membrane interactions.…”
mentioning
confidence: 99%
“…The unique intracellular targeting of each member allows for the spatial and temporal control of the synthesis of PI(4,5)P 2 , thereby regulating specific processes, such as endocytosis, actin assembly, formation of cell-cell contacts and adhesion to the extracellular matrix Heck et al, 2007;Ling et al, 2006;Schill and Anderson, 2009a). PI(4,5)P 2 influences physiological processes by binding to proteins containing domains such as the pleckstrin-homology (PH) domain, phox-homology (PX) domain, band 4.1 ezrin radixin moesin homology (FERM) domain or the Bin/ Amphiphysin/Rvs (BAR) domain to modulate their activities (Betson et al, 2002;Harlan et al, 1994;Lemmon et al, 2002;Toker, 2002;Yoon et al, 2012). In particular, PI(4,5)P 2 regulates various components of the endocytic and endosomal trafficking pathways, including epsin, AP180, dynamin, sorting nexins (SNXs), ARFs and clathrin adaptor protein complexes Martin, 2001;Schill and Anderson, 2009a;Seet and Hong, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, I-BAR proteins were observed to concentrate on constrictions of phagocytic cups, indicating their role in phagocytic uptake of pathogens [15]. Recent studies have reported a strong influence of PI(4,5)P 2 in the membrane deforming activity of BAR domain proteins [16].…”
Section: Membrane Curvature and Sorting At The Plasma Membranementioning
confidence: 96%